Key Factors in the Development of the ASEAN Logistics System - Quang Binh Dang; B. A. Anikin (Вестник университета)
Due to growing economy, investment, abundant labour force and tourism industry, the Association of Southeast Asian Nations (ASEAN) is becoming increasingly attractive to other parts of the world. ASEAN has a vast logistics system that contributes to the overall potential for development. The article examines key factors in the development of the ASEAN logistics system, the trends in the formation and ways of the effective development of logistics processes in the modern era of digitalization are revealed. The scientific novelty of the work lies in the fact that during a pandemic, digital technologies can contribute to the successful development of business in the logistics industry for ASEAN. In this regard, there is a need to focus the ASEAN region on automating the management of logistics processes, introducing and improving IT products, as well as on the needs of consumers and improving the quality of services provided.